The effect of core stability training on the balance ability of young male basketball players - Gong, J.; Sui, J.; Qi, F. (Frontiers in Physiology, 2024)
Introduction: This study aimed to investigate the impact of a 10-week Core Stability Training (CST) compared to Traditional Strength Training (TST) on the balance abilities of adolescent male basketball players.